Leaching of TCIPP from furniture foam is rapid and substantial. (February 2018) - Stubbings, William A.; Harrad, Stuart
Abstract: A series of laboratory experiments were conducted, in which waste furniture polyurethane foam samples containing tris (1-chloro-2-propyl) phosphate (TCIPP) were contacted with a range of leaching fluids, formulated to simulate the composition of landfill leachate. Leaching was examined under a number of different scenarios, such as: dissolved humic matter concentration, pH, and temperature, as well as the effect of agitation, and waste:leaching fluid contact duration. In addition to single batch (no replenishment of leaching fluid), serial batch (draining of leachate and replenishment with fresh leaching fluid at various time intervals) experiments were conducted. Leaching of TCIPP from PUF appears to be a first order process. Concentrations of TCIPP in leachate generated by the experiments in this study ranged from 13 mg L −1 to 130 mg L −1 . In serial batch leaching experiments, >95% of TCIPP was depleted from PUF after 168 h total contact with leaching fluid. Our experiments indicate leaching is potentially a very significant pathway of TCIPP emissions to the environment. Highlights: We study TCIPP leaching from furniture polyurethane foam (PUF). Leaching of TCIPP from PUF appears to be a first order process. In serial batch leaching tests, >95% of TCIPP was depleted from PUF after 168 h. TCIPP concentrations between 13 mg L −1 – 130 mg L −1 were detected in the leachate. Leaching is potentially a significant pathway of environmental TCIPP emissions.